2019
DOI: 10.1038/s41438-018-0096-0
|View full text |Cite
|
Sign up to set email alerts
|

Tomato lncRNA23468 functions as a competing endogenous RNA to modulate NBS-LRR genes by decoying miR482b in the tomato-Phytophthora infestans interaction

Abstract: Our previous studies indicated that tomato miR482b could negatively regulate the resistance of tomato to Phytophthora infestans and the expression of miR482b was decreased after inoculation with P. infestans. However, the mechanism by which the accumulation of miR482b is suppressed remains unclear. In this study, we wrote a program to identify 89 long noncoding RNA (lncRNA)-originated endogenous target mimics (eTMs) for 46 miRNAs from our RNA-Seq data. Three tomato lncRNAs, lncRNA23468, lncRNA01308 and lncRNA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
98
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(106 citation statements)
references
References 62 publications
(87 reference statements)
1
98
0
Order By: Relevance
“…This type of lncRNA is termed an endogenous target mimic (eTM) (Wu et al, 2013). Jiang et al (2019) reported that the tomato lncRNA23468 functions as an eTM to modulate NBS-LRR genes by mimicking miR482b in the tomato-P. infestans interaction. In this study, 12 lncRNAs were predicted to be target mimics of 17 known mature miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…This type of lncRNA is termed an endogenous target mimic (eTM) (Wu et al, 2013). Jiang et al (2019) reported that the tomato lncRNA23468 functions as an eTM to modulate NBS-LRR genes by mimicking miR482b in the tomato-P. infestans interaction. In this study, 12 lncRNAs were predicted to be target mimics of 17 known mature miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, several lncRNAs function by interacting with miRNAs in other plant species (Hao et al, 2015;Wang et al, 2015;Deng et al, 2018;Chen et al, 2018a). Furthermore, nta-eTMX27 in Nicotiana tabacum , osa-eTM160 in Oryza sativa (Wang et al, 2017a), lncRNA23468 in Solanum lycopersicum (Jiang et al, 2019), and LTCONS-00042843 in Dimocarpus longan (Chen et al, 2018a) are eTMs that modulate target gene expression by functioning as decoys for relevant miRNAs. The development of high-throughput sequencing and bioinformatics tools enabled the identification of many lncRNAs in several plant species, including model plants like A. thaliana (Yuan et al, 2016), O. sativa (Zhang et al, 2014;Wang et al, 2018a), and Brachypodium distachyon (Quattro et al, 2017), and also in horticultural plants such as S. lycopersicum (Zhu et al, 2015), Cucumis sativus (Hao et al, 2015), Musa itinerans (Liu et al, 2018a), D. longan (Chen et al, 2018a), and Citrus sinensis (Ke et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In A. thaliana, lncRNAs reportedly enhance the resistance to Pseudomonas syringae pv. tomato DC3000 by promoting PR1 expression [40]. In tomato, lncRNA23468 functions as a ceRNA that modulates NBS-LRR gene expression by mimicking the target of miR482b, thereby increasing the resistance to P. infestans [41].Walnut anthracnose has been responsible for the premature fruit drop and yield losses that have adversely affected walnut production in China [7].…”
Section: Discussionmentioning
confidence: 99%